Right approach: improvement in cleaning and disinfection of medical equipment in use – Sheikh Shakhbout Medical City (SSMC) experience - Emmanuel Fru Nsutebu; Reham Jafer Al Hajjeh; Prameela Maniamma Maniamma; Joselita L Rego; Mohammad Awwad (BMJ Open Quality)
Background In 2021, Sheikh Shakhbout Medical City (SSMC) faced an increase in hospital-onset multidrug-resistant organisms; Candida auris increased to 1.4 per 1000 patient days, within critical care areas. This rise prompted the infection prevention and control team to enhance cleaning and disinfection practices, aiming to reduce infection transmission risks. The focus was on adherence to a structured cleaning protocol, which included high standards of equipment disinfection, regular audits and the establishment of roles and responsibilities for staff involved in cleaning and disinfection.Methods To improve compliance, the team initiated regular audits starting in May 2021, which revealed an initial compliance rate of 49%. These audits assessed adherence to infection control standards for equipment cleaning, including the thoroughness of cleaning for high-touch areas on medical devices. A multidisciplinary team met regularly to develop a risk-based categorisation system for equipment, providing clear guidelines on cleaning practices. In parallel, targeted training programmes were rolled out for environmental service personnel and nurses. By October 2023, a tagging system was implemented to streamline protocols and improve adherence by marking equipment with specific cleaning instructions.Results The audits showed progressive improvements in compliance, reaching a peak of 100% by late 2022. However, staffing changes and turnovers affected adherence, with a temporary drop to 78% compliance in January 2023. The introduction of the tagging system in October 2023 contributed to a stabilised compliance rate exceeding 90% by early 2024, demonstrating the effectiveness of systematic interventions. The hospital-onset multidrug-resistant organism “C. auris” decreased to 0.5 per 1000 patient days in 2024.Discussion Transferring cleaning responsibilities and implementing new tools emphasised the need for continuous training and communication. The risk-based categorisation and tagging systems were particularly effective in reinforcing cleaning protocols, even as staff turnover posed challenges.Conclusions Through these strategic initiatives, SSMC significantly improved the cleaning and disinfection of medical equipment in critical care, reducing the presence of hospital-onset C. auris and enhancing patient safety. Ongoing evaluation and adaptation remain vital for sustaining high standards in infection control.